1994
DOI: 10.1002/rob.4620110604
|View full text |Cite
|
Sign up to set email alerts
|

Stability and traction control of an actively actuated micro‐rover

Abstract: This article addresses the issue of enhancing mobility of actively actuated vehicles by the use of optimal force distribution, and by actively controlling the location of the center of mass of the vehicle body. Force distribution in actively actuated vehicles is an underspecified problem, and optimal force distribution leads to improved contact conditions. Actively actuated vehicles also possess the ability to vary their configuration. This capability can be used to locate the center of mass of the system to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 8 publications
0
70
0
Order By: Relevance
“…Another possible factor is errors in the parameters used for the simulations. As shown in Fig 12(d), simulation results underestimated slip ratio s, which therefore means that v x is overestimated (see (1)). Based on (2), overestimation of v x provides underestimation of slip angle β.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Another possible factor is errors in the parameters used for the simulations. As shown in Fig 12(d), simulation results underestimated slip ratio s, which therefore means that v x is overestimated (see (1)). Based on (2), overestimation of v x provides underestimation of slip angle β.…”
Section: Resultsmentioning
confidence: 90%
“…Such rovers are called "reconfigurable robots" [2], and several studies have proved their potential to negotiate challenging terrain. Studies on reconfigurable rovers have thus far primarily focused on an improvement of their traction or rollover stability on rough terrain [1]- [3]. On the other hand, Wettergreen et al [4] showed experimentally that a downhill sideslip can be reduced by tilting a rover along the uphill direction when the rover traverses sandy slopes.…”
Section: Introductionmentioning
confidence: 99%
“…For wheeled rough terrain robots, enhanced performances can be obtained by maximizing the traction [2]. This allows getting the maximum from a rover in terms of obstacle climbing capability or minimizes its risk of getting stuck.…”
Section: A Related Workmentioning
confidence: 99%
“…For these systems researchers have proposed a number of approaches [3,7,8,9,11] that can be broadly classified as quasi-static stability approaches. In a quasi-static approach it is assumed that the vehicle motion relative to an inertial reference frame is slow (e.g., 1 m/s or less), therefore inertial accelerations can be neglected with the exception of gravitational acceleration.…”
Section: Related Workmentioning
confidence: 99%
“…As a result, the vehicle does not experience inertial forces that might trigger the tipover event. Approaches based on the support polygon are presented in [7,9,11]. These approaches suffer from the common problem of not measuring true cg motion while still assuming slow velocities.…”
Section: Related Workmentioning
confidence: 99%